(untitled) (Homoeopathy for All, 2024)
Worm infections continue to be among the most common diseases affecting children from low and middle income countries. Major worm infections of public health importance include Ascariasis, Trichuriasis, Hookworm, and Enterobiasis, which are transmitted through contaminated soil. Homeopathic medicines for worms help treat the problem naturally and are safe for use in children.